FUNCTIONAL GRAMMAR OF SYSTEMIC MENTAL PROCESS ANALYSIS IN KOREAN MOVIE MIRACLE IN CELL NO.7 - Nadya Puspita Riawan; Aflina Arifin (Universitas Negeri Medan, 2022)
This study is aimed to reveal and define the mental process occurred in the Korean movie “Miracle In Cell No. 7”. The mental process itself contained four sub types of process which are perceptive, cognitive, desiderative, and affective. The scope of the study is the researcher only focused on those four sub-types of mental process of systemic functional grammar. The researcher proposed M.A.K theory of systemic functional language as the main theory in doing this thesis. For this study, the researcher used movie script from website as the main object of this study. The researcher has described the process related to mental process of functional grammar. The results are; the researcher found 49 process of mental process occurred. As the final conclusion, the researcher concluded the percentage of each process as follow: cognitive with 14 (28.57), Affective with 12 (24.48%), and desiderative with 8 (16.34%). This result is valid based on the analysis of data and the classification of the types. The final result is that cognitive is the most dominant process of mental process occurred in the Miracle In Cell No. 7 movie.Keywords: Neologism, Social Networking, Acronym, Coinage.